MEMBANGUN EFFECTIVE SCHOOLS BERBASIS BUDAYA UNTUK MEWUJUDKAN PENDIDIKAN BERMUTU - Rabial Kanada (El-Idare, 2016)
The phenomenon of schools to maintain quality by adopting the principle that the quality of student input affect the realization of outcomes. They fall into their trap dimensional thinking on the concept of school excellence. It is, become fairness if done by private schools and to be a mistake when adopted by public schools, which is a manifestation of the state to ensure that all citizens receive a quality education. Education is a process of humanizing, so the school should receive multi character and abilities of children. The concept of such schools, upholds the differences that each child has kamampuan and different skills. The concept that gives equal opportunities to everyone to develop in accordance with each individual, so that in the process of input they receive children who are seen as the poor or low ability. Schools do ripening cultures growing quality of learners in ways that liberates learners from ignorance, helplessness, dishonesty, incompetence, and of bad character.